Archaeological mission at bat/al arid (MBA mission): 2023 season (4th season) wilāyā of ibri (dhahirah governorate) - Castel, Corinne (Athar: Bulletin of Archaeological Research in the Sultanate of Oman, 2025)
The project aims at enriching the debate on the nature of the settlement sites, the emergence of socio-economic complexity and the human-environment relationships in the Southern foothills region of Oman in the Early Bronze age. It is based on an extensive survey, a geoarchaeological and hydrological study in the region comprised between Al Arid and Bat (UNESCO site), and excavations at the recently discovered site of Al Arid (15 km NW of Bat). The approach is holistic and interdisciplinary and relies on specialists from the CNRS and universities, post-doctoral researchers and students. The team is composed of archaeologists, geoarchaeologists, hydrologists, biological anthropologists, geophysicist, archaeobotanist, specialists of pottery (formal typologies, physico-chemical and petrographic analyses of pastes), Geographic Information Systems and photogrammetry. After four seasons of work, we know that Al Arid was inhabited during two main phases: in the Early Bronze age and the Late Islamic period. In the Bronze age, the site appears as a regionally important centre. The discoveries are varied and sometimes exceptional: 7 towers concentrated on 25 ha, a material, local and exogen, including a superb copper alloy axe; from the beginning of the Bronze Age it seems: a copper metallurgical workshop, a canal for diverting the course of the wadi and 99 Hafit-type tombs among them two have been excavated ; dated to the Umm an-Nar period: a settlement sector (including a house that has been completely excavated), 9 tombs. These discoveries allow us to consider that communities lived there, on a recurrent, if not permanent basis, very early in history, relying on irrigation, a mastery of copper technology and exchanges with the coastal region and Mesopotamia. The mission is also heavily involved in the protection and enhancement of the region’s heritage, working alongside the Ministry of Heritage and Tourism on the Visitor Centre project of Bat.
Keywords: Archéologie – Oman